TI_GERICHTE 14.2004.17 vom 17. Dezember 2004 , Sequestro. Opposizione. Verosimiglianza credito. Beni detenuti dal debitore a titolo fiduciario. - TI Tribunale d'appello (2004)
Sequestro. Opposizione. Verosimiglianza credito. Beni detenuti dal debitore a titolo fiduciario.